Financial Behaviour and Financial Well-being of Tourism Workers in Sauraha, Nepal: A Comparative Study of Spending Patterns between Cash and Bank-based Salary Payments - Sharma, Bishnu (BIC Journal of Management, 2025)
This study evaluates the impact of salary payment methods— cash versus bank transfers—on the financial behaviour and financial well-being of tourism workers in Sauraha, Nepal. Financial well-being in this context refers to the ability of individuals to manage savings, control expenditures, and access formal financial services that contribute to economic resilience. Using a mixed-method approach, the research draws on survey data from 365 tourism workers and integrates statistical analysis with qualitative interviews to understand how different payment modes affect saving habits, financial inclusion, and spending discipline. Quantitative findings reveal that 94.2% of bank-paid workers reported regular savings, compared to only 69.8% among those paid in cash. A Chi-square test confirmed a statistically significant association between payment mode and saving behaviour (χ² = 31.981, p < .001), supported by Fisher’s Exact Test. Qualitative narratives further illustrated how digital payments promote financial control, reduce impulsive spending, and foster investment behaviours among previously unbanked workers. Conversely, barriers such as digital illiteracy and mistrust hinder adoption, particularly among field workers like elephant riders. These findings imply that transitioning to bank-based wage systems could enhance financial stability and should be supported by tourism policymakers, local government, and financial regulators through targeted digital financial literacy programs and accessible banking tools.